Lifestyle impact on serum level of vitamin D and PTH, in elderly - Ribeiro, Marta; Figueiredo, João; Gabriel, António (Millenium - Journal of Education, Technologies, and Health, 2017)
Introduction: The aging process is responsible for health decline and may lead to the dependence and consequent institutionalization. Bone metabolism involves serum calcium regulators, such as vitamin D and PTH. Objetives: The following study evaluated and compared serum concentrations of 25(OH)D and iPTH in elderly people living in institutions and living in their homes (free-living), with active and independent life. Methods: We evaluated 50 elderly (25 institutionalized and 25 not institutionalized). We made an individual questionnaire and we collected blood to measured the serum concentrations of iPTH and 25(OH)D. Results: Not institutionalized elderly showed higher 25(OH)D serum levels, comparing with institutionalized elderly (pvalue<0,05). The serum concentration of 25(OH)D was inversely correlated with iPTH. Furthermore calcium supplementation correlated with higher serum levels of 25(OH)D (p-value<0.05) and lower concentrations of iPTH (p-value<0,05). The free-living elderly who practice three or more activities per day, had higher concentrations of 25(OH)D (p-value<0.05) and lower concentrations of iPTH (p-value<0.05), compared to the institutionalized elderly. Outdoor activities showed also correlation with serum concentrations of both hormones (p-value<0.05). Conclusion: The adoption of an active lifestyle and the contact with nature, carry profit to a better aging process.